Development of smart mug with charging coaster using a peltier module and rechargeable battery - Muhammad Hanif Ikhwan, Razali (2017)
Demanding of beverages is increase in statistic around the world. Company like Starbuck and Dunkin’ Donut are among the company productivity affected by this phenomenon. The increase of intake of coffee, tea and other beverages increase the usage of cup either in the plastic, polystyrene or paper make a problem towards the environment. It will increase the number of dumping plastic or polysterene and also number of cutting down of tree. Besides, the usage of others mug such as ceramic mug did not become too efficient to overcome this problem since it cannot maintain the temperature and also be portable. Thus, a research is conduct to overcome the problem. This research is focused on inculcating all these characteristics and enables users to carry a multifunctional mug anywhere and everywhere. The Smart Mug with charging coaster as added values enables users to choose to prepare hot or cold water with onle need to press the button and it only takes around 45 minutes to be done the process. When the water or beverages reached the desired temperature, user will be able to consume the water directly from the Smart Mug. The Smart Mug is portable, reusable and affordable. Nowadays, people are looking for products which are cheap, efficient and long lasting. The goal of this project is to produce a controller circuit that can control the heating and cooling process of the Peltier Moudle and implying a proper rechargeable power supply for the system.